WEBSITE LPPM BERORIENTASI OBJEK PADA UNIVERSITAS BINA DARMA PALEMBANG (Universitas Bina Darma, 2013)
College is obliged to conduct research and community service, in addition to education. Institute for Research and Community Service Of Bina Darma University (LPPM-UBD) is an agency that coordinates research activities and community service and responsible to the Rector of the Bina Darma University. Processing research and community service at the University of Bina Darma has not been integrated in the software. In the process of sending a proposal or report is still done through the conventional paper media, CD, flashdisc and email. It also has not conducted an online promotion. To overcome this, the authors are interested in analyzing and designing Web LPPM-UBD using object-oriented method with the tool design using UML (Unified Modeling Language) and produce a prototyping (modeling) which is the implementation of the Website LPPM-UBD. Keywords: Unified Modelling Language, Prototyping and Object-Oriented Method